Relationship of culture and plant preferences among Malaysian / Noriah Othman, Masbiha Mat Isa and Noralizawati Mohamed - Othman, Noriah; Mat Isa, Masbiha; Mohamed, Noralizawati (Faculty of Architecture, Planning and Surveying, 2017)
Malaysia, being a country with a multiracial population is now in need of a range of information on appropriate and preferred environmental quality standards for providing both a habitable and aesthetically valued environment for its residents. The information needed should cover the diverse tastes; cultures and beliefs of the multi-racial community in order to create an environment preferred by the public that consist of different races. A study with respect to culture and plant preferences of landscape planting was carried out to compare the preferences of an urban multiracial community. There is a need to carry out such a study because urban planting in the city should reflect the multi-racial nature of society. Based on the human and plant relationship, the researcher can conclude that generally culture, experience and beliefs do play some roles in influencing one's preferences towards the plant selection. It is clear that in this study, generally all the respondents, regardless to which races they belong to, prefer landscape with plants which are properly maintained. The difference in their preference lies in terms of spatial arrangement of plants, type of plant categories (trees, shrubs and groundcovers), composition of plants and other elements such as colour, form, texture, order and plant hierarchy.